Analisis Intelijen Potensi Konflik dan Kekerasan di Johar Baru Dalam Perspektif Ancaman Wilayah di Provinsi DKI Jakarta - Manalu, Iwan Freddy (Jurnal Kajian Stratejik Ketahanan Nasional, 2020)
Conflicts brawl into a very intensive occurrence occurred in the district Johar Baru, DKI Jakarta. The brawlers are from teenagers forming a brawl gang. Through using qualitative research method, we began to know the mapping of conflict and the collective behavior as an action and reaction from conflict condition in Johar Baru sub-district comprehensively by intelligence analysis. Several factors trigger the occurrence of conflicts, especially social, economic and political factors make the brawl into one of the activities that belong to deviate from social norms and occur in a sustainable manner. In fact, it is alleged that the perpetuation of brawl activities among adolescents in the district of Johar Baru is an alibi of organized crime acts of drug dealer transactions in an area in the district Johar Baru. This intelligence analysis, adolescent torturing or somewhat similar here is analyzed from a social perspective to provide conflict resolution for citizens in the Johar Baru sub-district. Hence, we can do the mapping of opportunities and potentials of its citizens and develop strategies of weaknesses and obstacles encountered, referred to as SWOT analysis